Peer Gender and Mental Health - Demid Getik; Armando Meier (Lund University, School of Economics and Management, Department of Economics, 2021)
Adolescent mental health is key for later well-being. Yet, causal evidence on environmental drivers of adolescent mental health is scant. We study how an important classroom feature - the gender composition in compulsory-school - affects mental health. We use Swedish administrative data (N=576,285) to link variation in gender composition across classrooms within cohorts to mental health. We find that a higher share of female peers in a classroom increases the incidence of mental health diagnoses, particularly among boys. The effect persists into adulthood. Peer composition is thus an important and persistent driver of mental health.
Keywords: I12; I19; I21; I31; J16; J24; 330; gender; peer effects; mental health